Emerging approaches in predictive toxicology. (9th July 2014) - Zhang, Luoping; McHale, Cliona M.; Greene, Nigel; Snyder, Ronald D.; Rich, Ivan N.; Aardema, Marilyn J.; Roy, Shambhu; Pfuhler, Stefan; Venkatactahalam, Sundaresan
<x xml:space="preserve">Abstract</x> Predictive toxicology plays an important role in the assessment of toxicity of chemicals and the drug development process. While there are several well‐established in vitro and in vivo assays that are suitable for predictive toxicology, recent advances in high‐throughput analytical technologies and model systems are expected to have a major impact on the field of predictive toxicology. This commentary provides an overview of the state of the current science and a brief discussion on future perspectives for the field of predictive toxicology for human toxicity. Computational models for predictive toxicology, needs for further refinement and obstacles to expand computational models to include additional classes of chemical compounds are highlighted. Functional and comparative genomics approaches in predictive toxicology are discussed with an emphasis on successful utilization of recently developed model systems for high‐throughput analysis. The advantages of three‐dimensional model systems and stem cells and their use in predictive toxicology testing are also described. Environ. Mol. Mutagen. 55:679–688, 2014. © 2014 Wiley Periodicals, Inc.